Metabolism and pharmacokinetics of mebendazole in Japanese pufferfish (Takifugu rubripes). Issue 5 (4th May 2022) - Men, Lei; Zhang, Yuhan; Li, Keke; Li, Zhongyu; Li, Chunbin; Zhang, Xueyuan; Gong, Xiaojie; Fang, Linlin
Abstract: As a typical and broad-spectrum benzimidazole, mebendazole (MBZ) has long been used in human and veterinary medicine to treat parasitic infestations, and is widely employed in the aquaculture of Japanese pufferfish ( Takifugu rubripes ). However, there have been no studies examining the pharmacokinetic characteristics of MBZ in Japanese pufferfish. Furthermore, the presence of MBZ and its metabolites in animal-derived raw food represents a notable safety concern. Here, we investigated the metabolism of MBZ using a UPLC-Q-TOF system. Additionally, we evaluated the pharmacokinetics of MBZ and two metabolites, 2-amino-5(6)-benzoylbenzimidazole (MBZ-NH2 ) and 5-hydroxymebendazole (MBZ-OH), in Japanese pufferfish following intramuscular injection of 20 mg/kg MBZ. We detected three metabolites of MBZ (M1–M3), among which, 2-amino-5(6)-(a-hydroxybenzyl) benzimidazole (M3) was detected in an aquatic animal for the first time. The plasma dispositions of MBZ, MBZ-NH2, and MBZ-OH were characterized by low plasma clearance, medium distribution volume, and long terminal half-life. Moreover, these compounds were widely distributed in the muscle, from which they were rapidly cleared. The pharmacokinetics and metabolism of mebendazole in Japanese pufferfish are described for the first time in this study. Our findings provide a basis for the rational application of MBZ in Japanese pufferfish farming and contribute to our understanding of the metabolism of MBZ in cultured fish.